2019
DOI: 10.1016/j.cvex.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Examination and Corneal Surface Disease in the Ferret

Abstract: KEYWORDS Ferret Ophthalmology Cornea Mustela Corneal scar Eyes KEY POINTSOcular examination of the ferret can be challenging and requires a systematic approach.Ferret ophthalmic disease is uncommon.Ferrets eyes are small and relatively well protected but they can still experience corneal surface trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Horizontal pupils are usually only observed in prey species, regardless of activity pattern 14 . However, the ring‐tailed coati is mainly diurnal and presents a horizontally ovoid pupil, similar to that of ferrets 15 . However, with miosis it becomes teardrop shaped and obliquely oriented, with the most ventrotemporal portion being smaller and more ventral than its nasal portion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Horizontal pupils are usually only observed in prey species, regardless of activity pattern 14 . However, the ring‐tailed coati is mainly diurnal and presents a horizontally ovoid pupil, similar to that of ferrets 15 . However, with miosis it becomes teardrop shaped and obliquely oriented, with the most ventrotemporal portion being smaller and more ventral than its nasal portion.…”
Section: Discussionmentioning
confidence: 96%
“…14 However, the ring-tailed coati is mainly diurnal and presents a horizontally ovoid pupil, similar to that of ferrets. 15 However, with miosis it becomes teardrop shaped and obliquely oriented, with the most ventrotemporal portion being smaller and more ventral than its nasal portion. This unexpected finding was not a consequence of the rotation of the eye or the anesthesia; it was the actual shape of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…Banks et al [ 91 ], cited by Carvalho et al [ 70 ], reported that horizontal pupils are exclusively found in prey species, regardless of their activity pattern. In our analyzed red panda (a nocturnal and crepuscular animal), the pupil was horizontally ovoid, similar to that of the ring-tailed coati (mainly diurnal) and ferrets [ 70 , 93 ]. Kitchener et al [ 121 ] noted that in the subfamily Mustelinae, the pupil tends to be close to horizontal slits, likely corresponding to the horizontal visual streak characterized by high densities of photoreceptors in their retina and adjacent ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…10 Corneal dystrophy has not been reported to date. 11 A PubMed research on August 2023 with the words 'ferret corneal dystrophy' did not retrieve any results. The objective of this case report is to describe the clinical presentation, treatment and outcome of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Ferret ophthalmology has limited scientific literature to date and the described corneal diseases are limited to ulceration, lymphoplasmacytic keratitis, 9 nutritional deficiency of riboflavin causing corneal vascularisation and opacification 10 . Corneal dystrophy has not been reported to date 11 …”
Section: Introductionmentioning
confidence: 99%